A Quantum‐mechanical Study of the Binding Pocket of Proteorhodopsin: Absorption and Vibrational Spectra Modulated by Analogue Chromophores1. (25th July 2017) - Buda, Francesco; Keijer, Tom; Ganapathy, Srividya; de Grip, Willem J.
Abstract: Proteorhodopsin is a light‐driven proton pumping membrane protein related to bacteriorhodopsin. It contains an all‐ trans retinal A1 chromophore covalently bound to a lysine residue via a protonated Schiff base. In this study, we exploited density functional theory (DFT) calculations to investigate the retinal binding pocket in the dark state and after mimicking photoisomerization. The model of the binding pocket is constructed incrementally by adding the residues near the retinal that are necessary to ensure a stable protonated Schiff base. The presence of a few water molecules near the Schiff base turns out to be an essential feature of the model. The absorption properties are then studied using time‐dependent DFT (TDDFT) and compared to experimental data to further validate the structural model and to assess the accuracy of the computational setting. It is shown that TDDFT is able to reproduce the main absorption peak accurately and to quantitatively determine the spectral shift induced by substituting the native all‐ trans retinal A1 chromophore with different retinal analogues. Moreover, ab initio molecular dynamics simulations are performed to investigate the vibrational spectra of our models before and after isomerization. Specific differences in the vibrational spectra are identified that provide further insight into experimental FTIR difference spectra. Abstract : Green proteorhodopsins are a large class of light‐driven proton pumping membrane proteins. As no crystal structure is available for this system, we use a computational strategy based on DFT to build a model of the binding pocket from a homology structure. This minimal model is able to accurately predict the absorption spectrum for the native chromophore and the spectral shift induced by different retinal analogues. The crucial role of water molecules in the binding pocket and the hydrogen bond network rearrangement upon photoisomerization are also discussed.